An analysis of the forced recruitment of children, adolescents and young people (NNAJ) in the Departamento of Chocó, Colombia (Encuentros, 2022)
After 60 years of armed conflict in Colombia, a groundbreaking peace agreement was signed in 2016 between the FARC- EP guerrilla and the Colombian government. This agreement was endorsed by various international organizations and included progress on the restitution of the rights of child victims of forced recruitment. Five years after the signing of this agreement and with the FARC-EP’s disarmament process completed, it was expected that recruitment would be reduced in the areas where the guerrillas exercised control, however, this paper will show why this is not a closed issue. Mainly because the territories that had been occupied by the FARC-EP did not receive the institutional deployment that was expected, both on the part of the public forces and the institutional and social offer. The aim is to provide a general overview of the problem of forced recruitment in Colombia in order to detail its impact on the department of Chocó. This border region between Colombia and Panama has been plagued for years by an armed conflict that is still latent. The main historical milestones of recruitment and the dynamics of recruitment in the Colombian territories will also be reviewed.
Keywords: child soldiers, forced recruitment, recruitment dynamics.